Women's Representation in Pond's Age Miracle Advertisement “Perawatan Esktra untuk Kamu yang Luar Biasa” version on Youtube - Rahmawati, Fani Sania; An Nur, Fitrinanda; Deslia, Iva Fikrani (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
This research aims to esxplanation about women representation in Youtube channel. This research is a qualitative research, using qualitative analysis methods. Data collection techniques in this study using observations in the form of observations made at every place contained in advertisements, documentation, and literature studies, where the results of data collection will then be processed by researchers to obtain accurate and appropriate results. Age Miracle The version of "Perawatan ekstra untukmu yang luar biasa", women are represented as extraordinary figures, women are shown as active, independent, able to carry out activities outside the home, can work in the public sphere, can develop various skills and potentials. . but broadly speaking, this ad directs women to return to the domestic sector, as well as women's beauty